2004
DOI: 10.1021/jo048294k
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectively Nucleus and/or Side-Chain Fluorinated 2-(Phenanthryl)propionic Acids by an Effective Combination of Radical and Organometallic Chemistry

Abstract: Regioselectively nucleus and/or side-chain fluorinated 2-(phenanthr-1-yl)- and 2-(phenanthr-2-yl)propionic acids 1-5 were prepared using phenanthren-1(2H)-ones 6a-c as key intermediates. Thus, ethyl 2-(fluorophenanthryl)propionates 11 were obtained in good yields by Reformatsky reaction of 6a-c with ethyl 2-bromopropionate followed by dehydratation and DDQ-promoted aromatization of the resulting beta-hydroxyesters. Side-chain alkyl 2-hydroxy-2-(phenanthr-1-yl)propionates 14 were obtained by bromine/lithium per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Further, reduction of 41 with NaBH 4 provided alcohol 42 in 91% yield, which was then treated with DAST at 0 °C, afforded fluoride 43 in 73% yield (Scheme 5). 46 Reductive amination of 41 with NH 4 OAc and NaBH 3 CN under microwave irradiation (5 min, 130 °C) 47 yielded amine 44 in 72% yield.…”
Section: ■ Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Further, reduction of 41 with NaBH 4 provided alcohol 42 in 91% yield, which was then treated with DAST at 0 °C, afforded fluoride 43 in 73% yield (Scheme 5). 46 Reductive amination of 41 with NH 4 OAc and NaBH 3 CN under microwave irradiation (5 min, 130 °C) 47 yielded amine 44 in 72% yield.…”
Section: ■ Chemical Synthesismentioning
confidence: 99%
“…Meanwhile, the precursor 34 used for Schmidt rearrangement was also treated with acid 25a led to amide 41 lacking the lactam function in 54% yield. Further, reduction of 41 with NaBH 4 provided alcohol 42 in 91% yield, which was then treated with DAST at 0 °C, afforded fluoride 43 in 73% yield (Scheme ) . Reductive amination of 41 with NH 4 OAc and NaBH 3 CN under microwave irradiation (5 min, 130 °C) yielded amine 44 in 72% yield.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Therefore, since esters are refractory to this kind of fluorinating reagents, their conversion into a,a-difluoroalkyl/aryl ethers is made possible only after being transformed into the corresponding thioesters. In a previous research aimed at synthesizing some regioselectively fluorinated profens, we found that 2-aryl-2-fluoropropionic acid can be easily obtained from the corresponding 2-hydroxyesters by DAST-promoted OH/F permutation followed by alkaline hydrolysis of the resulting 2-fluoroester [22]. At the same time, we noticed that dialkyl 2-alkyl-2-fluoromalonates were prepared by exhaustive alcoholysis of hexafluoropropene followed by base-promoted alkylation of the resulting 2-fluoromalonates with alkyl halogenides [23] or, alternatively, by fluorination of dialkyl 2-alkylsodiomalonates with either Xenon difluoride [24] or electrophilic NF fluorinating reagents [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Their potentially interesting properties were first pointed out by Ricci and Ruzziconi, who elaborated a general approach to the synthesis of 2-phenanthryl-2-fluoropropionic and 2-phenanthrylperfluoropropionic esters and acids. [7] Apart from their contribution, there are currently no general methods to access 2-arylperfluoropropionic Abstract: Hexafluoropropene reacts with aromatic azine N-oxides under mild conditions to produce fluorides of 2-heteroarylperfluoropropionic acids. The reaction proceeds as 1,3-dipolar cycloaddition followed by spontaneous scission of the NÀO bond in the isoxazolidine ring and elimination of HF.…”
Section: Introductionmentioning
confidence: 99%